Interreligious Tolerance in Kerta Buana Village, Tenggarong Seberang District - Lugan, Stepanus; Lio, Zakeus Daeng; Nampar, Hilario Didakus Nenga (Budapest International Research and Critics University, 2022)
This study examines inter-religious tolerance. The current situation shows that inter-religious tolerance in homogeneous community groups is decreasing. This study focuses on the experience and practice of tolerance in Kerta Buana Village to prevent socio-religious conflicts. This study uses a qualitative approach with a combination of interview, observation, and documentation methods to collect data from four informants. The data collected was then analyzed descriptively. The findings show that the practice of tolerance among religious believers is an active practice of tolerance by respecting, respecting, being open in accepting differences and cooperating with each other in building a harmonious and tolerant religious life. This practice forms a harmony-based model of tolerance, namely: a multicultural society, consisting of various religions (Hinduism, Islam, Protestantism, Catholicism, Buddhism, and Confucianism), and various ethnicities (such as Balinese, Sasak, Javanese, Batak, Minahasa, Toraja, Sunda, Sumbawa, Bali-Lombok, Banjar, Madura, Chinese, Flores, Dayak, Kutai) who live together and in harmony; a sense of shared destiny, is the awareness that is born in individuals and groups to build coexistence both among religious believers and between ethnic transmigrants, including local transmigrants and local residents; awareness of harmony, is a way to invite the community to build a culture of tolerance, both in the local and wider community. More specifically, the experience and practice of inter-religious tolerance in Kerta Buana can be a reference for the catechesis of human brotherhood